ОРДЕНОТ SOLEM IMPERII MACEDONIÆ НА СВЕТСКИОТ МАКЕДОНСКИ КОНГРЕС / THE ORDER SOLEM IMPERII MACEDONIÆ OF THE WORLD MACEDONIAN CONGRESS - George Goce Durtanoski (Македонски хералд - Macedonian Herald, 2019)
This article provides a broaderexplanation of the design, processing,inauguration, and eventual suspensionof the highest award of the WorldMacedonian Congress, the Order of theSun of the Macedonian Empire (SolemImperii Macedoniæ), an associate insigniaof the honorary title Macedonian Senator(Macedonica Senatoris) bestowed upon foreignand domestic activists, lobbyists, and friends ofMacedonia for achievements that contribute tostrengthening Macedonia’s international positionas an independent and sovereign state.The full name of the order is Order of the Sun ofthe Macedonian Empire Grand Collar and PurpleRibbon (in Macedonian: Орден Сонце на маке-донската империја со голем ѓердан и пурпур-на лента; in French: L’ordre du Soleil de l’empiremacédonien avec un grand collier à ruban pourpre).The Latin name is Solem Imperii Macedoniæ. TheOrder is awarded in one rank and has been awardedtwice: in January 2004 to Robert Badinter in Parisand in February 2004 to Otto von Habsburg inSkopje.